Fire Retardancy and Leaching Resistance of Furfurylated Pine Wood (Pinus sylvestris L.) Treated with Guanyl-Urea Phosphate - Lin, Chia-Feng; Karlsson, Olov; Kim, Injeong; Myronycheva, Olena; Mensah, Rhoda Afriyie; Försth, Michael; Das, Oisik; Mantanis, George I.; Jones, Dennis; Sandberg, Dick (Polymers, 2022)
Guanyl-urea phosphate (GUP) was introduced into furfurylated wood in order to improve fire retardancy. Modified wood was produced via vacuum-pressure impregnation of the GUP–furfuryl alcohol (FA) aqueous solution, which was then polymerized at elevated temperature. The water leaching resistance of the treated wood was tested according to European standard EN 84, while the leached water was analyzed using ultra-performance liquid chromatography (UPLC) and inductively coupled plasma–sector field mass spectrometry (ICP-SFMS). This new type of furfurylated wood was further characterized in the laboratory by evaluating its morphology and elemental composition using optical microscopy and electron microscopy coupled with energy-dispersive X-ray spectrometry (SEM-EDX). The chemical functionality was detected using infrared spectroscopy (FTIR), and the fire resistance was tested using cone calorimetry. The dimensional stability was evaluated in wet–dry soaking cycle tests, along with the mechanical properties, such as the Brinell hardness and bending strength. The fire retardancy of the modified furfurylated wood indicated that the flammability of wood can be depressed to some extent by introducing GUP. This was reflected in an observed reduction in heat release rate (HRR2) from 454.8 to 264.9 kW/m2, without a reduction in the material properties. In addition, this leaching-resistant furfurylated wood exhibited higher fire retardancy compared to conventional furfurylated wood. A potential method for producing fire-retardant treated furfurylated wood stable to water exposure has been suggested. Validerad;2022;Nivå 2;2022-05-02 (hanlid); Funder: CT WOOD, Luleå University of Technology; European Structural and Investment Fund, OP RDE (CZ.02.1.01/0.0/0.0/16_019/0000803); Part of special issue: Performance and Application of Novel Biocomposites II Advanced Research Supporting the Forestry and Wood Processing Sector’s Adaptation to Global Change and the 4th Industrial Revolution